CHALLENGES OF PROVING CHANGE OF CUSTOMARY PERSONAL LAW IN INTESTATE SUCCESSION IN NIGERIA: RE-VISITING OLOWU .V. OLOWU AND THE CONCEPT OF ACCULTURATION - Omolola, Mohammed-Lawal Kafilat; Oluwakemi, Akanbi Khairat (JOURNAL EQUITABLE, 2025)
The rules governing change of personal law are usually domicile, change of nationality or change of religion depending on the nature of personal law. However the Supreme Court of Nigeria in Olowu v. Olowu recognised that personal law could also be changed by the adoption of a new culture; a process described by the Supreme as culturalization/acculturation. Inspite of the innovation introduced through this decision, the decision did not include a proper criteria for determining when a person could be said to have changed his culture. This paper therefore examined the general criteria for change of personal law under the conflict of laws and their relevance to change of customary law. The study found that while the principle of acculturation is an important innovation, the absence of clear guidelines for its application could impair its effectiveness. It was recommended that other principles that are used to determine change of personal law under conflict of law rules have become fairly certain having benefited from long usage and consistent judicial pronouncement. Acculturation on the other hand has not accrued the benefits of long usage. However leaving its subsequent development to judicial pronouncement could further complicate its development. It is therefore recommended that legislative intervention is necessary to regulate its development. This would ensure consistency and certainty of the law.